Chinese idioms and traditional chinese medicine - Anwen Zheng (Wolters Kluwer Health/LWW, 2018)
Like traditional Chinese medicine, Cheng Yu can also be viewed as a brilliant facet of traditional Chinese culture. In the essay, the author attempts to illustrate the close link between the two through some examples.